First visualization of circulating neutrophil extracellular traps using cell fluorescence during human septic shock-induced disseminated intravascular coagulation. Issue 183 (November 2019) - Stiel, Laure; Mayeur-Rousse, Caroline; Helms, Julie; Meziani, Ferhat; Mauvieux, Laurent
Abstract: Disseminated intravascular coagulation (DIC) is a severe complication of septic shock. Polymorphonuclear neutrophils (PMNs) may play a key role in septic shock-induced DIC via the release of neutrophils extracellular traps (NETs). NETs capture invading pathogens, but also act as a pro-coagulant surface at the interface between immunity and thrombosis. During septic shock-induced DIC, neutrophil activation may result in excessive NET formation. Herein, we originally report the presence of circulating NETs in human blood during septic shock-induced DIC. To investigate NET formation during shock-induced DIC neutrophils were isolated from patients in septic shock associated with ( n  = 3) or without ( n  = 3) DIC. Neutrophils from healthy donors ( n  = 3) were stimulated in vitro with ionomycin as NET formation positive controls. PMNs smears were stained with mouse anti-human FITC anti-myeloperoxidase antibody and the blue-fluorescent DAPI nucleic acid stain. NETs were identified as elongated extracellular DNA fibers associated to myeloperoxidase detected by immunofluorescence. NETs were unambiguously observed in PMNs from septic shock patients with DIC but not from patients without DIC. NETs features in DIC+ patients were undistinguishable from those observed in ionomycin-induced PMNs from healthy donors. Fluorescence images of NETs were associated to extracellular cytoplasmic expansions. Our data report for the first time the direct visualization of circulating NETs in patients with septic shock-induced DIC. The in vivo relevance of previously reported indirect markers of NETosis (neutrophil side fluorescence) is confirmed. Highlights: Netosis features can be detected in blood PMNs using simple fluorescence microscopy. PMNs purified from patients with DIC-induced septic shock display NETosis features. Morphological analysis of PMNs can distinguish septic shock patients with DIC.